Effects of different strains fermentation on nutritional functional components and flavor compounds of sweet potato slurry - Long Pan; Cun-Jin Zhang; Zhe Bai; Ying-Ying Liu; Yu Zhang; Wei-Zhi Tian; Yu Zhou; Yuan-Yuan Zhou; Ai-Mei Liao; Yin-Chen Hou; Guang-Hai Yu; Ming Hui; et al. (Frontiers in Nutrition, 2023)
In this paper, we study the effect of microbial fermentation on the nutrient composition and flavor of sweet potato slurry, different strains of Aspergillus niger, Saccharomyces cerevisiae, Lactobacillus plantarum, Bacillus coagulans, Bacillus subtilis, Lactobacillus acidophilus, and Bifidobacterium brevis were employed to ferment sweet potato slurry. After 48 h of fermentation with different strains (10% inoculation amount), we compared the effects of several strains on the nutritional and functional constituents (protein, soluble dietary fiber, organic acid, soluble sugar, total polyphenol, free amino acid, and sensory characteristics). The results demonstrated that the total sugar level of sweet potato slurry fell significantly after fermentation by various strains, indicating that these strains can utilize the nutritious components of sweet potato slurry for fermentation. The slurry’s total protein and phenol concentrations increased significantly, and many strains demonstrated excellent fermentation performance. The pH of the slurry dropped from 6.78 to 3.28 to 5.95 after fermentation. The fermentation broth contained 17 free amino acids, and the change in free amino acid content is closely correlated with the flavor of the sweet potato fermentation slurry. The gas chromatography-mass spectrometry results reveal that microbial fermentation can effectively increase the kinds and concentration of flavor components in sweet potato slurry, enhancing its flavor and flavor profile. The results demonstrated that Aspergillus niger fermentation of sweet potato slurry might greatly enhance protein and total phenolic content, which is crucial in enhancing nutrition. However, Bacillus coagulans fermentation can enhance the concentration of free amino acids in sweet potato slurry by 64.83%, with a significant rise in fresh and sweet amino acids. After fermentation by Bacillus coagulans, the concentration of lactic acid and volatile flavor substances also achieved its highest level, which can considerably enhance its flavor. The above results showed that Aspergillus niger and Bacillus coagulans could be the ideal strains for sweet potato slurry fermentation.